Direct in vitro and in vivo demonstration of muscarinic receptor binding by the novel radioligand, [3H]5-hydroxymethyltolterodine, in the bladder and other tissues of rats - Shizuo Yamada; Shiori Kuraoka; Yoshihiko Ito; Satomi Kagota; Kazumasa Shinozuka; Satomi Onoue (Elsevier, 2020)
In vitro and in vivo binding sites of [3H]-labeled 5-hydroxymethyltolterodine (5-HMT), a new radioligand for labeling muscarinic receptors in rat tissues were characterized. Specific [3H]5-HMT binding in rat tissues was saturable and of high affinity in each tissue. The dissociation constant (Kd) was significantly lower in bladder and heart than in submaxillary gland. Significant levels of in vivo specific [3H]5-HMT binding by intravenous injection of the radioligand were detected in tissues, except for cerebral cortex. Thus, [3H]5-HMT was shown to specifically label muscarinic receptors in rat tissues, suggesting a useful radioligand for labeling muscarinic receptors with high affinity. Keywords: [3H]5-HMT, Bladder, Muscarinic receptor